Angular BN-Heteroacenes with syn-Structure-Induced Promising Properties as Host Materials of Blue Organic Light-Emitting Diodes - Zhang, Wanzheng; Zhang, Fan; Tang, Ruizhi; Fu, Yubin; Wang, Xinyang; Zhuang, Xiaodong; He, Gufeng; Feng, Xinliang (Organic Letters, 2016)
A series of novel angular BN-heteroacenes were successfully synthesized. Associated with the intrinsic syn-structures, they exhibit unique molecular alignments in a solid state and promising electronic properties, and are thus suitable as efficient nondoped emitters for the fabrication of blue organic light-emitting diodes with improved performance.
CRIS-Team Scopus Importer:2023-03-20